Deficiências minerais em vacas em lactação da bacia leiteira do município de Rondon do Pará, estado do Pará - BOMJARDIM, Henrique dos Anjos (2015)
A study of mineral deficiencies was performed in lactating cows from dairy herds belonging to 13 farms of Rondon do Pará, state of Pará, Brazil. We determined the levels of phosphorus (P) in the bone and levels of copper (Cu), cobalt (Co), selenium (Se) and zinc (Zn) in the liver of 47 dairy cows in lactation 2. The samples were collected by means of biopsies taken on the top third of the 12th rib of the right side and the caudal edge of the caudate liver lobe, respectively. The herds were composed of crossbred (Holstein x Zebu) cattle, kept in extensive production system on Brachiaria brizantha cv. Marandu pasture and received mineral supplementation. The mineral mixture on 12 farms were commercial type, called "full" and the owners added a quantity of salt above the manufacturer's recommendations on ten farms. The mineral mixtures were provided in troughs without covering on seven farms and on other eight, providing of the mineral mix was not performed daily. On 11 farms there were clinical histories consistent with mineral deficiencies in livestock, and placenta retention and osteophagia were the most frequently reported ones. The results of chemical analysis showed deficiency of P on five farms, of Co on three farms, of Se on nine farms and of Zn on ten farms. It is concluded that the mineral supplementation performed on the farms do not supply the daily demands of P, Se and Co, based on the estimated daily consumption of 30g of NaCl per animal; the little adequate or inadequate troughs for proper supplementation, as well as inconstant supply of mineral mixtures contribute to the deficiency of one or more minerals.